Kinetic modelling of wet peroxide oxidation with N-doped carbon nanotubes - Díaz de Tuesta, Jose Luis (2020)
Carbon nanotubes (CNT) were tested as catalysts in the removal of 2-nitrophenol (2-NP) by catalytic wet peroxide oxidation (CWPO). The CNT materials were synthesized by catalytic chemical vapour deposition in a fluidized-bed reactor, as described elsewhere [1,2]. In order to synthesize a CNT with different characteristics, ethylene and acetylene were feeding as follows: 1) ethylene for 30 min (resulting in catalyst E30); 2) acetonitrile for 20 min, followed by ethylene for 20 min (A20E20); 3) acetonitrile for 20 min, followed by ethylene for 10 min (A20E10); 4) ethylene for 10 min, followed by acetonitrile for 20 min (E10A20); or 5) acetonitrile alone for 30 min (A30). These CNT were tested in CWPO adopting the experimental procedures reported in our previous studies [2-3] and at the following operating conditions: 50 ºC, pH0 = 3.0, 0.25 g L-1 of catalyst, 0.5 g L-1 2-NP and 1.78 g L-1 of added hydrogen peroxide (H2O2). Power-law kinetic equations were fitted to experimental data, following a similar statistical regression described elsewhere [4]. Results are depicted in Figure 1.